The Etiology of Chest Pain in Children Admitted to Cardiology Clinics and the Use Echocardiography to Screen for Cardiac Chest Pain in Children - Chen, Li; Duan, Hongzhou; Li, Gang; Li, Xiaoyan (Frontiers in Pediatrics, 2022)
Aims Chest pain is a common complaint in pediatric cardiology clinics. For the diagnosis of children's chest pain, most cardiac specialists choose to use echocardiography to evaluate the etiology of and screen for children's cardiac chest pain. We analyzed the etiology and echocardiography results of children with chest pain in pediatric cardiology clinics, clarified the disease spectrum and evaluated the diagnostic value of echocardiography in screening cardiac chest pain in children. Methods and Results We retrospectively analyzed the clinical data of patients aged younger than 18 years who visited Beijing Anzhen Hospital for chest pain between 2005 and 2019. We divided the patients into the preschool group, the school-age group and the adolescent group and analyzed the sex distribution. Based on auxiliary exams and clinical diagnoses, we developed the disease spectrum of children's chest pain and calculated the diagnostic value of echocardiography in screening children's cardiac chest pain. A total of 3477 children were included in this study. Chest pain was of cardiac origin in 232 patients (6.7%) and noncardiac origin in 3245 patients (93.3%). The incidence of noncardiac chest pain was significantly higher in the preschool group and the school-age group than in the adolescent group (94.9% vs. 94.3% vs. 91.4%, respectively, P<0.05). In the preschool group, most of the patients were girls (51.4%), while in the school-age group and the adolescent group, most of the patients were boys (P < 0.05). Among the children (n = 3205) who underwent echocardiography, 108 children had positive results, and 3097 children had negative results. Among the 108 positive results, 10 cases of cardiac diseases were related to chest pain. The sensitivity, specificity, positive predictive value and negative predictive value of echocardiography in the diagnosis of cardiogenic chest pain were 6.7%, 96.9%, 12.96% and 93.67%, respectively. Conclusions In children with chest pain who are admitted to pediatric cardiology clinics, chest pain is mostly benign and rarely due to cardiac diseases. The use of echocardiography in evaluating cardiac chest pain in children is of little diagnostic utility and contributes to additional costs for patients and the health care system.